Pengaruh Pengetahuan Perpajakan, Persepsi Mahasiswa, Self-Efficacy, dan Pertimbangan Pasar Kerja Terhadap Minat Berkarir di Bidang Perpajakan pada Mahasiswa Akuntansi Universitas Balikpapan - Jane Monica Devi Alifia Sheren; Yudea; Dika Karlinda Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The research aims to identify the influence of tax knowledge, student perception, self-efficacy, and job market considerations on career interest in taxation in accounting students of the University of Balikpapan. The research was conducted at the University of Balikpapan. The research uses primary data types with data collection techniques through the distribution of questionnaires in google forms and directly. The sampling method used is the Purposive Sampling and the sample obtained was 166 respondents. The data analysis methods used in the study are Partial Least Square-Structure Equation Model (PLS-SEM) with the smartPLS3.0 application. The results of the study show that tax knowledge, student perception, self-efficacy, and the consideration of the job market each affects the interest in a career in taxation in accounting students of the University of Balikpapan.